Improving the Photoelectrochemical Performance of Hematite by Employing a High Surface Area Scaffold and Engineering Solid–Solid Interfaces. Issue 7 (19th January 2016) - Chakthranont, Pongkarn; Pinaud, Blaise A.; Seitz, Linsey C.; Forman, Arnold J.; Jaramillo, Thomas F.
Abstract : Herein, a high surface area electrode (HSE) consisting of indium tin oxide (ITO) as a scaffold and ultrathin Ti‐doped hematite (α‐Fe2 O3 ) as the absorber material is developed. The HSE exhibits sixfold improvement in photoactivity over an analogous photoelectrode with a flat morphology. Interfacial recombination due to dopant impurities and shunting resulting from a high pinhole density in the hematite layer limit the device performance. These limitations are mitigated by introducing a tin oxide barrier layer, which reduces recombination at the solid–solid interface and mitigates shunting. Employing the HSE with an appropriate barrier layer improves charge separation efficiency and catalytic activity compared to conventional planar devices. This strategy can potentially be extended to other light absorber materials whose performance is affected by charge transport limitations. Abstract : High surface area electrodes (HSE) consisting of high surface area indium tin oxide (ITO) scaffolds coated with Ti‐doped hematite (α‐Fe2 O3 ) as the absorber material are developed. The addition of a tin oxide barrier layer on the HSE device mitigates solid–solid interfacial recombination and shunting, yielding a sixfold improvement in photocurrent density compared to conventional planar devices.